Analysis of the Internal Control System for Rice Inventory - Purba, Alan Smith; Hamdana; Narishwari , Urianda (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This study uses a qualitative case study method to analyze the internal control system for rice inventory at Perum Bulog, East Kalimantan Regional Division, Balikpapan City. Data were collected through observation, interviews, and documentation studies. The key informants in this study were three main participants, namely the warehouse head, operational officer, and admin, who have important roles in inventory management. The results of the study indicate that the internal control system implemented at Perum Bulog Balikpapan is not yet fully optimal. The El Nino phenomenon exacerbates the situation by adding complexity to rice inventory management. Limited human resources (HR), inconsistent use of the Enterprise Resource Planning (ERP) system, and lack of training and understanding of internal control procedures are the main obstacles in maintaining the accuracy and efficiency of inventory management. Implementation of a more integrated system and improvement of human resources capacity are needed to strengthen internal control and ensure success in managing rice supplies in the future